Brokerage of Bandwidth Commodities - CHELIOTIS, Giorgos (Institutional Knowledge at Singapore Management University, 2000)
There exist several websites today where buyers and sellers of point-to-point connectivity and telephony minutes can post bids and offers, respectively. Owing to the convergence of data and voice technologies and the emergence of IP as a universal service substrate, trading of IP-based connectivity is receiving increased attention lately. In [Che99] a hierarchical trading model for bandwidth commodities was introduced, and the computational complexity of brokerage in a spot market for bandwidth was studied. A step further, we now discuss the benefits and risks associated with bandwidth brokerage, in a first attempt to evaluate the effects on bandwidth trading of a secondary market for composite contracts, which we call "path contracts".